Dietary supplements in the sport - Zdunek, Roksana; Strus, Karolina; Madera, Magdalena; Mazur, Sylwia; Marcinkowski, Krzysztof; Dąbrowska, Natalia; Nagórska, Emilia; Kublińska, Aleksandra (Quality in Sport, 2024)
In recent years, the popularity of dietary supplements among athletes has surged, often aimed at enhancing sports performance and improving training outcomes. However, along with this popularity comes an increasing risk of using substances classified as doping in sports. This article examines the current state of knowledge regarding dietary supplements used by athletes, considering the potential risk of violating anti-doping regulations. The article discuss popular ingredients such creatine, beta-alanine, branched-chain amino acids and others.